Diseño para una aplicación para dispositivos móviles que difundan los mitos y leyendas de la serranía ecuatoriana de las ciudades de Latacunga, Ambato, Riobamba) - Tapia Flores, Andrea Stephani (2015)
This research study aims to encourage the use of multimedia platforms such as APP (Computer Application Mobile), which will help students studying technological processes interact with data transmission within the area of Computer Graphics Design, these new applications allow the user to transfer and access to information published on the website, since it is based on theoretical, scientific and practical foundations for a better development of students with these applications. During the preparation of the application (APP) myths and legends knowledge strengthens ancestral stories of cities: Latacunga, Ambato, Riobamba, and with the help of technological resources and training it was possible to create a tool of creative and interactive digital media. The mobile application will help spread the myths and legends of the cities mentioned, which is published in the APP store (Play Store, Android, Samsung), and it is also developed to be published in the store (App Store, iOS, iPhone) for the user to download and thus can interact digitally with your mobile device.